Blood glucose levels in a population of healthy, breast fed, term infants of appropriate size for gestational age - Hoseth, E. (BMJ Group, 2000)
AIM—To determine blood glucose levels in a population of healthy, breast fed, term infants of appropriate size for gestational age. METHODS—In a cross sectional study, the blood glucose concentration of 223 healthy, breast fed, term infants of appropriate size for gestational age was determined at different times (between one and 96 hours) after delivery. One sample of blood glucose was taken from each infant independent of the feeding time. The glucose concentration was correlated with sex, method of delivery, delivery with or without analgesia, smoking status of the mother, gestational age, umbilical cord pH, and Apgar score. Infants suspected of suffering from intrapartum hypoxia were excluded. RESULTS—Blood glucose concentration one hour after delivery was not significantly lower than at any other time. Only two infants had low blood glucose concentrations one hour after delivery (1.4and 1.9 mmol/l). There were no significant differences in blood glucose concentration between sexes, methods of delivery, infants delivered with or without analgesia, and infants born to smokers or non-smokers, and there was no further correlation between blood glucose concentration and gestational age, umbilical cord pH, or Apgar score. DISCUSSION—Very few healthy, breast fed, term infants of appropriate size for gestational age have low blood glucose levels, and there is no indication for blood glucose monitoring in these infants.